Complex histories of repeated gene flow in Cameroon crater lake cichlids cast doubt on one of the clearest examples of sympatric speciation. (1st June 2015) - Martin, Christopher H.; Cutler, Joseph S.; Friel, John P.; Dening Touokong, Cyrille; Coop, Graham; Wainwright, Peter C.
Abstract: One of the most celebrated examples of sympatric speciation in nature are monophyletic radiations of cichlid fishes endemic to Cameroon crater lakes. However, phylogenetic inference of monophyly may not detect complex colonization histories involving some allopatric isolation, such as double invasions obscured by genome‐wide gene flow. Population genomic approaches are better suited to test hypotheses of sympatric speciation in these cases. Here, we use comprehensive sampling from all four sympatric crater lake cichlid radiations in Cameroon and outgroups across Africa combined with next‐generation sequencing to genotype tens of thousands of SNPs. We find considerable evidence of gene flow between all four radiations and neighboring riverine populations after initial colonization. In a few cases, some sympatric species are more closely related to outgroups than others, consistent with secondary gene flow facilitating their speciation. Our results do not rule out sympatric speciation in Cameroon cichlids, but rather reveal a complex history of speciation with gene flow, including allopatric and sympatric phases, resulting in both reproductively isolated species and incipient species complexes. The best remaining non‐cichlid examples of sympatric speciation all involve assortative mating within microhabitats. We speculate that this feature may be necessary to complete the process of sympatric speciation in nature.